Case Report: Successful treatment of a novel variant of CARD14-mutated juvenile Pityriasis rubra pilaris with ixekizumab - Millak, Laura; Hahn, Matthias; Fischer, Judith; Volc, Sebastian (Frontiers in Medicine, 2025)
Pityriasis rubra pilaris is a rare inflammatory papulosquamous skin disease without any approved treatment options. Variants in the CARD14 (caspase recruitment domain family member 14) gene have been identified to play a role in the pathophysiology of atypical juvenile PRP by activating the IL-23/IL-17A cytokine axis, highlighting this pathway as a potential target of therapy. Here, we present a case of successful treatment with ixekizumab, a humanized monoclonal anti-IL-17A antibody, in an atypical juvenile PRP (type V) patient with a novel variant of CARD14 mutation.